Open-Framework Structure Based Cathode Materials Coupled with Metallic Anodes for Rechargeable Multivalent Ion Batteries. Issue 16 (10th December 2020) - Xiong, Ya; Lin, Yueqiang; Xue, Qingzhong
Abstract : Rechargeable batteries based on multivalent chemistry represent a promising avenue in grid-scale and portable energy storage devices, especially when multivalent metal with high energy density is used as the anode. Owing to the unique advantages of large 3D diffusion channels, multiple oxidation states of metal ions, and the ability to modulate the size of the intercalation channels for multivalent ions (Zn 2+, Mg 2+, Al 2+, Ca 2+ ) intercalation/deintercalation, open framework materials are regarded as ideal cathodes. Herein, this review firstly provides an introduction of recent open-framework structure based cathode materials including Prussian blue and its analogs (PB/PBAs), NASICONs, Zinc vanadate (zinc pyrovanadate, e.g., Zn3 V2 O7 (OH)2 ·2H2 O and α -Zn2 V2 O7, zinc n-vanadate, e.g., Zn(OH)VO4 ), and Molybdenum-vanadium oxide (Mo2.5+y VO9+z ) along with a presentation of their energy storage mechanisms. Afterwards, representative examples of such intercalated materials applied to multivalent ion batteries are considered. Some strategies to further improve the electrochemical performances of open-framework structure based cathode materials are also presented. Finally, the challenges and development directions of these materials in rechargeable multivalent ion battery systems are discussed.